(untitled) (The Review of Diabetic Studies, 2024)
Health literacy represents an essential dimension of holistic health, emphasizing the individual’s ability to understand, process, and apply health information in ways that promote well-being. Among healthcare workers, this competency supports clearer communication with patients, safer clinical decision-making, and improved care coordination. A holistic lens acknowledges that health literacy extends beyond knowledge to include motivation, confidence, and the capacity to navigate complex systems (Engle et al., 2021). When organizations support the development of health literacy, they empower healthcare staff to work more effectively with patients from diverse backgrounds. This investment ultimately strengthens patient outcomes and contributes to overall system performance, aligning with broader principles of sustainable, high-quality care (Warner et al., 2020).